2017
DOI: 10.3389/fphar.2017.00757
|View full text |Cite
|
Sign up to set email alerts
|

Ketogal: A Derivative Ketorolac Molecule with Minor Ulcerogenic and Renal Toxicity

Abstract: Ketorolac is a powerful non-steroidal anti-inflammatory drug (NSAID), with a great analgesic activity, present on the Italian market since 1991. Despite the excellent therapeutic activity, the chronic use of ketorolac has long been limited owing to the high incidence of gastrointestinal and kidney side events. In our previous study, we demonstrated that ketorolac–galactose conjugate (ketogal), synthesized and tested in a single-dose study, was able to reduce ulcerogenicity, while preserving the high pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Once it was established that ketogal did not induce oxidative stress in the lower GI tract, consistent with most clinical studies of NSAIDs, we demonstrated the safer profile of ketogal compared with ketorolac in the other organs as well, particularly in the upper GI tract [3,7] and in the liver [16,17]. Consistently, we examined histopathological changes after repeated oral treatment in mice with ketorolac and ketogal, under the conditions previously adopted for the stomach and kidneys in our past work [31].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Once it was established that ketogal did not induce oxidative stress in the lower GI tract, consistent with most clinical studies of NSAIDs, we demonstrated the safer profile of ketogal compared with ketorolac in the other organs as well, particularly in the upper GI tract [3,7] and in the liver [16,17]. Consistently, we examined histopathological changes after repeated oral treatment in mice with ketorolac and ketogal, under the conditions previously adopted for the stomach and kidneys in our past work [31].…”
Section: Discussionsupporting
confidence: 77%
“…The results obtained for the small intestine, liver, and, previously, for the stomach and kidneys [31], demonstrate that ketogal undoubtedly has the potential to overcome most of the side effects associated with repeated administration of ketorolac. Indeed, its toxicological profile has consistently exceeded expectations in in vivo and ex vivo models [31,32].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations